Kegiatan Pengabdian Kepada Masyarakat - Deteksi Dini Penyakit Metabolik Melalui Penapisan Gula Darah, Asam Urat Dan Komposisi Tubuh Pada Populasi Dewasa - Santoso, Alexander Halim; Kurniawan, Joshua; Gaofman, Brian Albert; Lumintang, Valentino Gilbert; Jaya, I Made Satya Pramana; Rayhan, Naufal (Journal Of Human And Education (JAHE), 2024)
The human body consists of four components at the molecular level: water, fat, protein and minerals. As we age, there can be an increase in fat mass and a decrease in muscle mass. A high proportion of body fat has a greater risk of cardiovascular disease, obesity, type 2 diabetes, several types of cancer, and premature death. Diabetes mellitus is a chronic disease characterised by increased blood sugar levels due to impaired insulin metabolism. Uncontrolled type 2 diabetes mellitus can result in significant complications such as cardiovascular disease, diabetic nephropathy (kidneys), diabetic retinopathy (eyes), neuropathy (nerves), and impaired wound healing. Hyperuricemia is an increase in uric acid levels above normal values. Hyperuricemia can increase the risk of cardiovascular disease, metabolic syndrome, and kidney stones. We conducted this early detection activity at Kalam Kudus Middle School, where the average age of the participants was 39 years. Based on the examination results, the average results for blood sugar levels, uric acid, total body fat, total body subcutaneous fat, visceral fat, and total body muscle mass were each 90 mg/dL; 4.9 mg/dL; 33.5%; 27.4%; 9%; and 24.8%. Through this activity, participants can understand the risk factors for metabolic diseases such as diabetes, hyperuremia and obesity, especially their impact on health status problems. We expect this activity to significantly improve the health and quality of life of participants.